The performance of two-implant overdentures in the atrophic maxilla: a case series with 1-year follow-up - Pieter Onclin; Caroline M. Speksnijder; Henny J. A. Meijer; Arjan Vissink; Gerry M. Raghoebar (SpringerOpen, 2022)
Abstract Purpose To assess the implant and prosthesis survival rates, the clinical, radiographical and patient-related outcome measures, and the masticatory performance of maxillary overdentures supported by two implants in patients with an atrophic maxilla. Methods In this case series, 15 consecutive patients who were eligible for maxillary implant overdenture therapy, but who had insufficient bone volume to place at least four implants and were unwilling to be treated with reconstructive surgery were asked to participate. After giving consent, participants received two implants in the maxilla under local anaesthesia. After 3 months of osseointegration, a maxillary overdenture with palatal coverage and solitary attachments was fabricated. Implant and overdenture survival, marginal bone level change, clinical outcome measures, masticatory performance and patient-related outcomes were evaluated at baseline and 1 year after overdenture placement. Results Fourteen out of 15 participants completed the follow-up period of 12 months. Implant and overdenture survival rate were 89.3% and 85.7%, respectively. Change in marginal bone level (− 0.5 ± 0.7 mm), change in probing depth (0.0 ± 1.0 mm), and clinical outcomes were favourable. Masticatory performance and patient-related outcomes improved significantly compared to baseline. Complications were minimal. Conclusions Within the limitations of this study, it can be concluded that patients with extreme resorption of the maxilla that are unwilling to be treated with reconstructive surgery, benefit from two-implant maxillary overdentures retained by solitary attachments in terms of improved masticatory functioning and denture satisfaction. However, they have relatively high risk of implant loss. Trial registration: UMCG Trial Register (RR201900060), registered 22 January 2019. Graphical Abstract